The Linda Kizazi study: a comparison of morbidity and mortality from birth to 2 years between children who are HIV-unexposed and HIV-exposed, uninfected in the era of universal antiretroviral therapy - John Kinuthia; Dara A Lehman; Dalton Wamalwa; Brenda Wandika; Emily R Begnel; Ednah Ojee; Judy Adhiambo; Eliza Mabele; Vincent Ogweno; Efrem S Lim; Soren Gantt; Jennifer Slyker (BMJ Global Health, 2025)
Background Historically, children who are HIV-exposed, uninfected (CHEU) have been found to have greater morbidity and mortality than children who are HIV-unexposed, uninfected (CHUU). To assess whether this difference persists in the era of universal antiretroviral therapy (ART), we conducted a cohort study to compare the risk of acute diarrhoea, respiratory tract infections (RTI), malaria, hospitalisation, and all-cause mortality between Kenyan CHEU and CHUU from birth to 2 years.Methods From December 2018 to March 2020 at Mathare North Health Centre in Nairobi, we recruited pregnant women living with HIV on ART for ≥6 months and pregnant women without HIV from the same community. We followed the mother–infant pairs for 2 years post partum and collected data on symptoms of illness, clinical visits and diagnoses, and infant feeding every 3 months; a self-selected subset of participants also received weekly data collection for up to 1 year. We compared the risk of each outcome between CHEU versus CHUU using HRs from Andersen-Gill (recurrent morbidity outcomes) and Cox proportional hazards (mortality) regression models adjusted for maternal age, marital status and education level.Results Among 187 mother–infant pairs with postpartum data, 86 (46%) infants were CHEU and 101 (54%) were CHUU. All initiated breastfeeding, and 88% of CHEU and 57% of CHUU were exclusively breastfed (EBF) for ≥6 months. There was no significant difference in risk of diarrhoea (HR=0.79, 95% CI 0.52 to 1.22), malaria (HR=0.44, 95% CI 0.16 to 1.21), hospitalisation (HR=1.11, 95% CI 0.30 to 4.14), or mortality (HR=1.87, 95% CI 0.17 to 20.5). However, CHEU had lower risk of any RTI (HR=0.60, 95% CI 0.44 to 0.82) and pneumonia (HR=0.29, 95% CI 0.091 to 0.89).Conclusions CHEU born to women on effective long-term ART experienced similar overall morbidity and mortality as CHUU. However, CHEU had substantially lower risk of pneumonia and other RTI, possibly due to longer EBF in this group.